On a perturbation theorem of Kaiser and Weis - Batty, C (2005)
We improve a perturbation theorem of C. Kaiser and L. Weis for semigroups of operators on Hilbert spaces by using a generation theorem of A.M. Gomilko, D.H. Shi and D.X. Feng. © 2005 Springer.